INOVASI PEMBELAJARAN MUFRODAT MENGGUNAKAN MEDIA WORDWALL BERBASIS GAME BASED LEARNING - M. Fikri Nurhadi; Wasilah; Irmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Vocabulary learning (mufrodat) is a fundamental component in mastering the Arabic language; however, instructional practices at the elementary school level often rely on conventional methods such as memorization and repetitive drills without engaging contextualization. These conditions result in low interest and motivation among learners, as observed in Grade VI Salafiyah Ula Ma’had Za’adul Ma’ad Palembang. Limited variation in instructional media and strategies contributes to low learning engagement and suboptimal learning outcomes. As an effort to introduce instructional innovation, this study implements Wordwall media based on Game Based Learning as an innovative alternative in teaching mufrodat. This innovation offers an interactive learning experience through various educational games that enable students to learn actively, enjoyably, and in a structured manner. The study aims to analyze the effectiveness of using Wordwall media integrated with Game Based Learning on students’ motivation and mufrodat learning outcomes. Through the application of this innovative media, students demonstrated increased interest, active participation, and better vocabulary comprehension compared to previous methods. The findings affirm that the innovative use of interactive digital, game-based media can serve as an effective solution to enhance the quality of Arabic language instruction in elementary schools, particularly in vocabulary learning.